Neutrality of Public Officials in Elections based on The Perspective of General Principles of Good Governance - Sulistyowati, Sulistyowati; Prasetyo, Mas Subagyo Eko; Maharaja, Gusti Bintang; Andika, Andi (Law Development Journal, 2024)
A clean and competent government applies the general principles of good government. Neutrality is one of the general principles of good government that every state official must uphold. Neutrality of public officials means not taking sides or engaging in practical political interests, especially in elections. This study aims to analyze the problems related to public officials' neutrality in Indonesia and provide solutions to ensure that neutrality. This study uses qualitative methods with a normative approach. The data used are secondary in the form of legislation, official documents, literature, and relevant previous research results. The results showed that the main problems related to public officials' neutrality in Indonesia are public officials' low awareness and understanding about the importance of neutrality, weak supervision, sanctions against neutrality violations, and the pressure and intervention of certain interested parties. Solutions that can be provided to ensure the neutrality of public officials in Indonesia are to increase socialization and education about neutrality, strengthen monitoring and enforcement mechanisms against neutrality violations, and build a culture of integrity and professionalism among public officials. Vigorous law enforcement is the solution.